Traditional Arts, Spirituality and The Challenges of Modernity: A Study of The Samman Dance in Sumenep, Madura - Rozaki, Abdur; Suaidi, Suaidi (International Journal of Islamicate Social Studies, 2024)
Samman ritual dance in Sumenep, Madura, is a cultural heritage reflecting the harmonious integration of spirituality and social life in Sufistic Islam. As an artistic expression rich in symbolism, this dance serves as a medium of worship to God and as a tool of social glue within the local community. This research explores two main dimensions of Samman dance: spiritual value and social value. Spiritual value is seen in the harmony of movement, music, and singing, which creates a contemplative space and strengthens the human relationship with the Creator. Meanwhile, social value is manifested through collective participation, solidarity between individuals, and respect for local traditions that enhance the cultural identity of the Madurese community. However, the challenges of modernization, such as the commodification of culture in tourism, can potentially reduce the sacred meaning of this dance. Through descriptive-empirical and qualitative approaches, this study analyses the function of ritual as a dynamic spiritual and social medium. The study concludes that Samman Dance preservation efforts require a holistic strategy involving local communities, the government, and the younger generation to balance traditional preservation and modern innovation. With this approach, Samman Dance can continue to thrive as a symbol of cultural and spiritual wealth that is relevant in the contemporary era.